Factors related to coronavirus infection in workers at fast-track basic health units - Alencar, Suzy Romere Silva de; Silva, Nádia Maria Pires; Barbosa, Nanielle Silva; Ferreira, João Caio Silva Castro; Silva, João Felipe Tinto; Leal, Samira Rêgo Martins de Deus (Revista de Enfermagem da UFPI, 2023)
Objective: To identify the factors related to infection by the new coronavirus in workers of fast-track basic health units. Methods: Cross-sectional study carried out in the capital of Piauí with 114 health workers in four fast-track basic units between August and November 2021. Questionnaires were applied with sociodemographic, occupational and performance-related variables during the COVID-19 pandemic. Data were analyzed using descriptive and inferential statistics. A significance level of 0.05 was adopted. Results: Among the sample, 93.9% tested for COVID-19, and 48.2% of them had a positive result. The most used protective equipments were: surgical mask (92.1%), caps (87.7%) and procedure/sterile gloves (64.0%). Regarding access to biosafety training, the participants said they had participated in training for the placement and removal of PPE (57.9%) and hand hygiene (64%). Regarding the use of the N95 mask or similar, 28.9% said they did not use it. Conclusion: Ensuring access to protective equipment of sufficient quality and quantity, the rational use of these inputs, proper handling and disposal and actions aimed at avoiding physical and emotional exhaustion of workers are fundamental strategies to overcome the crisis and preserve the health of these individuals.